WHEN THE SILENCE PREVAILS IMAGES TALK: THE CHARACTERISTIC CT FEATURES OF VOCAL CORD PARALYSIS, CAUSES OF MISSED PALSY BY RADIOLOGISTS AND MIMICS OF VOCAL CORD PALSY UNVEILED - Mariam Malik,; Salma Gul,; Belqees Yawar Faiz, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Causes of vocal cord palsy (VCP) can be identified even before its clinical presentation if a radiologist has knowledge about signs of vocal cord palsy, its various mimics and the anatomy of recurrent laryngeal nerve. Objectives are to know the signs and underlying causes leading to VCP and various mimics which may lead to the false positive diagnosis of VCP. Methods: A retrospective cross-sectional pilot study comprising 54 patients with vocal cord palsy proven by IDL was conducted. 3 groups were identified. The first group comprised missed VCP on cross-sectional imaging. The second group was, of missed cause of VCP in patients with clinical diagnoses. The third group was patients with mimics of the palsy. Results:Thirteen (76.5%) patients had missed diagnosis due to lack of knowledge of signs and 23.5% due to lack of time, overwork and tiredness. A vigilant search for the cause was not done in 31.6% of patients and in 68.4% of patients, the cause was identified but not correlated. A total of 8 patients had false positive diagnoses due to failure to differentiate from mimics. Conclusion: There is an increasing trend of missed diagnosis of vocal cord palsy on cross-sectional imaging in patients with established clinical diagnosis due to a lack of knowledge of VCP signs and missed causes along the course of recurrent laryngeal nerve.